(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Introduction: to increase the effectiveness of treatment of patients with staghorn and multiple nephrolithiasis by improving percutaneous nephrolithotripsy using a multi-access method. Methods: 29 patients with staghorn and multiple kidney stones, aged 15 to 63 (29.3±4.3) years, were treated. The average stone size was 65.4±5.2 mm. Results: in 20 patients (69.0%), the operation was performed through 2 accesses, in 8 (27.6%) - through 3, and in 1 (3.4%) - through 4 accesses. The duration of operations was, on average, 109.3±6.4 minutes. 26 (89.7%) patients were completely (stone free) free from kidney stones. In 3 (10.3%) patients, residual stones were left. Intraoperative complications were observed in 3 (10.3%) patients, postoperative complications - in 7 (24.1%). Conclusion: Multi-access PCNL is an effective treatment for staghorn and multiple kidney stones.